PKM Pelatihan Mitigasi Bencana Alam bagi Siswa SMAN 3 Solok - Riko Maiyudi; Yoszi Mingsi Anaperta; Facrul Rozi Ramadhan; Tri Gamela Saldy; Harizona Aulia Rahman; Rizto Salia Zakri (Departemen Teknik Pertambangan FT UNP, 2019)
Abstract. Natural disasters in recent years are very common and need preparedness, awareness and vigilance in the face of disaster, especially in the city of Solok, starting from earthquakes, landslides and other. To reduce the risk of disaster management is required in accordance with law number 24 year 2007 about disaster management.The absence of disaster mitigation training provided for students in particular SMA N 3 Solok and less optimal students ' role/young generation in disaster mitigation because students have not had the knowledge to mitigate make the dedication to conduct training mitigation and preparedness of disaster to them so that the participants understand about how mitigation and preparedness. This training is provided in the form of lectures, discussions, and field practices.After training was obtained the increase of knowledge about the mitigation of natural disasters by the students SMAN 3 Solok. At pre-training (before training) only 65.8% of students who understand the mitigation of natural disasters and at the time of post-training increased to 96.2% of students understand the mitigation of natural disasters..Keywords: Natural disasters, disaster management, mitigation and preparedness